A revisit to the Higo terrane, Kyushu, Japan: The eastern extension of the North China–South China collision zone. (1st August 2017) - Suga, Kenshi; Yui, Tzen-Fu; Miyazaki, Kazuhiro; Sakata, Shuhei; Hirata, Takafumi; Fukuyama, Mayuko
Graphical abstract: Highlights: The North China–South China collision zone extends eastward into the Higo subduction terrane. The protoliths of the Higo terrane are Triassic–Jurassic subduction complexes. The proto-Japan was located close to the North China craton. Abstract: The Higo and Manotani high- T metamorphic rocks belong to the Higo terrane, central Kyushu, Japan. This terrane has been suggested as the eastern extension of the North China–South China collision zone based mainly on the similar petrological and geochronological data to the north Dabie high-grade rocks. In this study, detrital zircon U–Pb dating for the Higo metamorphic rocks yielded a maximum depositional age of 197 Ma with a prominent component at 193–284 Ma (62–95%) and a subsidiary peak at 1847–1875 Ma (19–28%); whereas for the Manotani metamorphic rocks, the maximum depositional age is 263 Ma with a prominent component at 263–304 Ma (98%). These results suggest that the protoliths of the Higo and Manotani metamorphic rocks might be equivalent to those of the early–middle Jurassic Chizu and late Triassic Suo high- P metamorphic rocks, southwest Japan, respectively. The absence of middle Neoproterozoic detrital zircon ( c . 700–825 Ma) is incompatible with a proposition that the proto-Japan might have been located close to the South China craton, where Permian–Jurassic sedimentary rocks contain a significant amount of middle Neoproterozoic detrital zircon. The zircon provenance of the Higo terrane, as well as of the Chizu and Suo belts, could therefore be the North China craton, suggesting that the Suo metamorphic rocks, including the Manotani metamorphic rocks, have formed at the subduction plate boundary in the east, which changed into the contemporaneous North China–South China collision plate boundary in the west, likely passing through the Korean Peninsula. The transformation of the Chizu and Suo metamorphic rocks to the Higo and Manotani metamorphic rocks can be accounted for by the oceanward advance of the volcanic arc during trench retreating. The Cretaceous high- T metamorphism and related igneous intrusions of the Higo terrane would be regarded as the initial phase of the Ryoke event.